Understanding and improving functionality of waxy wheat flours - Garimella Purna, Shivananda Kumar (Kansas State University, 2010)
To realize the full potential of waxy wheat flours in food applications, six advanced hard waxy wheat lines were studied. Pasting properties of waxy wheat flours as well as factors governing the pasting properties were investigated. Waxy wheat starch granules swelled more extensively and were more prone to α-amylase degradation than normal wheat starch. A combination of endogenous α-amylase activity and protein matrix contributed to a large variation of pasting properties of waxy wheat flours. Bi-axial extension properties classified dough from waxy wheat as in-elastic. Waxy wheat flour had higher water absorption and lower mixing time than normal wheat flour. Waxy wheat starch affected protein hydration but not protein extractability after optimum dough mixing. Presence of some non-protein free thiol contents and some gliadins acting as chain terminators could be the underlying reasons for waxy wheat flours producing slack dough. In an effort to improve functionality of waxy wheat flours, hydro-thermal processing was used. Two temperatures (140 and 160°C), three moisture contents (0, 12.4 and 20%), and four exposure times (0, 5, 15, 30 and 60 min) were employed. Hydrothermal processing resulted in non-cohesive waxy wheat flours with high viscosity and greater acid stability than native waxy wheat flour. A closer investigation revealed the possible role of endosperm proteins in improving pasting properties of waxy wheat flours. Upon thermal processing, waxy wheat flours demonstrated a long hydration time before forming dough. Heating decreased protein solubility while no changes in starch molecular weight distribution were observed. Our results indicate that hydro-thermal processing results in increased starch protein interaction. As part of application of waxy wheat, bread was baked by replacing normal wheat flour with two hard waxy wheat flours at 15, 30, and 45% levels. Substitution with waxy wheat flour resulted in higher loaf volume and softer loaves. However, substitution at > 30% resulted in excessive post-bake shrinkage and a ‘key-hole’ shape with an open crumb structure. Bread crumb microstructure indicated a loss of starch granule rigidity and fusing of starch granules. Soluble starch content was significantly higher in bread 1-day old crumb containing waxy wheat flour than in control bread.
Keywords: Waxy wheat; Pasting; Flour Modification; Hydrothermal Treatment; Rheology; Baking; Agriculture, Food Science and Technology (0359)